Under ground water Assessment in Diyala Bridge Area - ., کمال برزان ندا; ., غفران فاروق جمعة; ., احمد عبد الله (Iraqi Journal of Civil Engineering, 2012)
Severe Shortage and bad quality of Surface water in the area of Diyala Bridge , added to the growing demand for drinking , irrigation and sanitary waters , leads to study and qualify the under ground water in this area , Six shallow wells has been selected to the east of Diyala river , five of them where on shore and the sixth was far away from river about ( 3 km) .The depth of these wells was (10- 14)m . Tests of ( Ph , TDS , BOD , Turbidity , Conductivity ,----etc) where performed during March , June, Aug. in 2008. Heavy metals such as ( Pd , Zn , Cd , Fe , Mn ) has been examined as well . Results of physical , chemical and bacteriological tests show that the water quality of these wells were not comply with WHO requirements ,as well as results show considerable increased concentrations in TDS,BOD and heavy metals which indicates that underground waters were highly polluted with the sanitary waste waters . On the other hand the on shore wells' water quality was very close to the river water quality in comparison with the well in the middle of the town.